EPIDEMIOLOGY, ETIOLOGY, AND PATHOGENESIS OF HARD DENTAL TISSUE DISEASES. (International journal of artificial intelligence, 2026)
Hard dental tissue diseases, particularly dental caries, remain among the most prevalent chronic diseases worldwide and continue to represent a major public health challenge. According to recent global epidemiological data, billions of people are affected by oral diseases, with dental caries being the most widespread condition among both children and adults. The prevalence of caries is especially high in developing countries, where inadequate oral hygiene, unhealthy dietary habits, and limited preventive measures contribute significantly to disease progression. Dental caries is a multifactorial disease associated with bacterial biofilm activity, demineralization of enamel, and destruction of hard dental tissues. This article reviews the epidemiology, etiology, and pathogenesis of hard dental tissue diseases and highlights the importance of preventive strategies, early diagnosis, and modern technological approaches in improving oral healthcare outcomes.